Ekonomi dan Politik Pendekatan Maqasid Syariah - Mifti Ibdalia; Muhammad Albahi (Economic Reviews Journal, 2025)
Economics and politics are two important aspects that shape the structure of human social life. In Islam, these two fields are not only seen as a means to achieve material prosperity, but also as a means to achieve prosperity in this world and the hereafter. For this reason, the approach used in economics and politics must be in line with sharia principles, which are based on larger goals, namely maqasid sharia. Maqasid Syariah, which literally means "goals of sharia", refers to five aspects The main things that must be maintained in human life are religion (deen), soul (nafs), reason (aql), heredity (nasl), and wealth (mal). This approach emphasizes the importance of creating a harmonious, just and prosperous life, by prioritizing a balance between material and spiritual needs. In this context, maqasid sharia provides guidance for building an economic system that does not only prioritize material profits, but also focuses on social equality and justice. Likewise in politics, maqasid sharia emphasizes the importance of justice, protection of human rights and people's welfare. The maqasid sharia approach in economics and politics aims to create a system that is based on Islamic moral and ethical values, which prioritizes the welfare of the people and the sustainability of life. Therefore, the application of these principles in economic and political policies is important in realizing a just and prosperous society. In this article, we will discuss further how the maqasid sharia approach can be applied in economics and politics to achieve the goal of holistic welfare of the people.